Is There BN Bond‐Length Alternation in 1, 2:3, 4:5, 6‐Tris(biphenylylene)borazines?. Issue 9 (17th May 2013) - Müller, Matthias; Maichle‐Mössmer, Cäcilia; Sirsch, Peter; Bettinger, Holger F.
Abstract: The alternation of the BN bonds in the central borazine ring of the overcrowded 1, 2:3, 4:5, 6‐tris(biphenylylene)borazine (2 a ) and its tribromo derivative (2 g ) is investigated by computational methods and compared with their experimentally obtained crystal structures. The calculations are performed with a meta‐generalized‐gradient‐approximation (GGA) density functional (Tao–Perdew–Staroverov–Scuseria (TPSS)) without and with dispersion corrections, including Becke–Johnson damping, in conjunction with a polarized triple‐ζ basis set. These data show a small bond‐length alternation (BLA) of around 0.01 Å in2 a and2 g . This outcome is in good agreement with X‐ray diffraction data for2 g, but at variance with earlier X‐ray diffraction measurements that gave a BLA of 0.06 Å for2 a . A re‐investigation of the crystal structure of2 a reveals a positional disorder that precludes a discussion of the BN bond lengths. The synthesis of2 g is the first example of an electrophilic aromatic substitution of an aryl borazine with elemental bromine. Successful bromination was also demonstrated for hexaphenylborazine. Abstract : All things being equal : The electrophilic aromatic bromination of 1, 2:3, 4:5, 6‐tris(biphenylylene)borazine yields the tribromo derivative that has only small bond‐length alternation (BLA) according to X‐ray crystallography and state‐of‐the art computations (see scheme). A re‐investigation of the structure of the parent 1, 2:3, 4:5, 6‐tris(biphenylylene)borazine compound by experiment and theory reveals positional disorder of the borazine core.